Endogenous and exogenous risk factors in the success of South African small medium enterprises - Galawe, Ntombikayise Jabulile (My University, 2017)
The objective of this study is twofold: first to evaluate the magnitude of the effect of endogenous and exogenous risk factors in the success of South African (SA) small and medium-sized enterprises (SMEs); second, to develop a framework for an integrated risk assessment model that can be used to assess SA SMEs holistically. Drawing from the entrepreneurial ecosystem, systems perspective, GEM framework and complex theory, an integrated risk assessment model framework that is person-centric, interdisciplinary, and multidimensional (individual, firm and environment) is formulated. This was a cross-sectional, quantitative study, which followed a post-positivist approach. Primary data, with a sample size of 286, was collected from SA SMEs through self-administered questionnaires. Data analysis included correlational analysis, backward elimination method, hierarchical multiple regression and mediation analysis. Financial capital, entrepreneurial self-efficacy on growth and risk perception emerged as significant predictors of SME success. However financial capital is by far the most influential predictor of financial performance. The results also confirmed the mediating effect of financial capital between entrepreneurial self-efficacy (finance and growth) and financial performance. Entrepreneurs who are confident can raise enough capital for their businesses, thus producing successful SMEs. Government policies and support programmes need to take a holistic view when supporting SMEs. While taking a holistic view, priority needs to be put on making capital available for entrepreneurs to develop and grow their businesses. Training programmes can focus on up-skilling entrepreneurs regarding entrepreneurial tasks that can improve their self-efficacy in management, financial understanding, and growth of their businesses. The study’s findings are important in that they help funders realise that business plans and financial projections are not the most important predictors of SME success, thus the need to review current risk assessment models.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, South Africa, in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) March 2017
Keywords: Small business--South Africa; Business enterprises--South Africa; Success in business--South Africa; Risk management--South Africa